Conditionally Reprogrammed Cells and Robotic High-Throughput Screening for Precision Cancer Therapy - Alkhilaiwi, Faris (Frontiers in Oncology, 2021)
Cancer is a devastating disease that takes the lives of millions of people globally every year. Precision cancer therapy is based on a patient’s tumor histopathology, expression analyses, and/or tumor RNA or DNA analysis. Only 2%–20% of patients with solid tumors benefit from genomics-based precision oncology. Therefore, functional diagnostics and patient-derived cancer models are needed for precision cancer therapy. In this review, we will summarize the potential use of conditional cell reprogramming (CR) and robotic high-throughput screening in precision cancer medicine. Briefly, the CR method includes the co-culturing of irradiated Swiss-3T3-J2 mouse fibroblast cells alongside digested primary non-pathogenic or pathogenic cells with the existence of Rho-associated serine–threonine protein kinase inhibitor called Y-27632, creating an exterior culture environment, allowing the cells to have the ability to gain partial properties of stem cells. On the other hand, quantitative high-throughput screening (qHTS) assays screen thousands of compounds that use cells in a short period of time. The combination of both technologies has the potential to become a driving force for precision cancer therapy.